Reconciling Customary Debt and Islamic Economic Law: A Legal-Anthropological Study of Mappajalang Dowi' in Tolitoli, Indonesia - B., M. Taufan; Marzuki, Marzuki; Nasaruddin, Nasaruddin; Amrullah, Amiruddin (Jurnal Ilmiah Al-Syir'ah, 2025)
This article analyzes mappajalang dowi', a harvest-linked debt practice among Bugis farmers in Puse, Tolitoli, through a legal-anthropological lens that connects Islamic legal doctrine with community practice. Limited access to salaried employment and formal financial services sustains villagers' dependence on pre-harvest borrowing, with repayment due after the harvest season. Based on a qualitative case study employing observation, in-depth interviews, and document analysis, this research reconstructs the contractual structure of the practice, particularly ijab–kabul, mutual expectations, and the proportional ziyādah (increase) that may rise when repayment is delayed. A normative assessment grounded in classical Islamic jurisprudence covering benevolent lending (qardh al-hasan), gratuitous transactions (tabarru'), and unlawful gain (riba), as well as contemporary Indonesian Sharia economic regulations and fatwas, shows that the pre-agreed ziyādah converts the arrangement into a benefit-bearing loan and therefore constitutes indicators of riba. To maintain both Sharia compliance and rural social solidarity, the study proposes alternatives such as genuine benevolent lending with explicit anti-promise clauses, the use of sale-based contracts like salam and murābahah for agricultural inputs, and the establishment of community tabarru' funds. The study presents a context-sensitive framework for enhancing Islamic economic practices in agrarian smallholder contexts.